Diagnosis of Trialeurodes vaporariorum (Homoptera: Aleyrodidae) in tobacco and kidney beans of Garcia Rovira, Santander - PEREA-A., ERIKA l.; ROJAS-M., ELEONORA; VILLALOBOS-M., ALFONSO (Revista Colombiana de Entomología, 2003)
Tria/eurodes vaporariorum (Westwood) is a sucking insect of major economic importance in tobacco and kidney beans crops of García Rovira Province (Santander), Colombia. A diagnosis of the T. vaporariorum (whitefly) problem was done by polling farmers and technicians in the area. Additionally, visual scales were used in order to estímate the level of damage and infestation of the crops. Kidney bean growers identify the whitefly as the principal pest in their crops. and associated its presence with the occurrence of fumagine (Capnodium sp.). Among the interviewed farmers. 60% reported the loss of one half of the harvest because of the whitefly. Nevertheless, 40% completely abandoned their crops. Tobacco crops were found in relatively good conditions and only shaded areas had signs of infestation. One hundred percent of those surveyed use chemical products for pest control. A lack of documentation and the presence of several different crops in one area limits the accuracy and specificity of the technical assistance provided to the farmers for whitefly control. Most (95%) of crops visited revealed high populations of whitefly (more than 1.000 individuals per leaf) and 88% presented signs of severe damages by fumagine.